2016
DOI: 10.1136/openhrt-2016-000415
|View full text |Cite
|
Sign up to set email alerts
|

Variabilities in the mortality-related resource utilisation for congenital heart disease

Abstract: ObjectiveOur objective was to characterise the divergence of effort from outcome in congenital heart disease (CHD) care by measuring mortality-related resource utilisation fraction (MRRUF) for various CHD lesions across institutions of differing volumes.MethodsStudy design was observational analysis of an administrative database, the Pediatric Health Information System (PHIS). The setting was inpatient; 2004–2013. Patients were ≤21 years old with atrial septal defect (ASD), ventricular septal defect (VSD), tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Despite surgical repair during childhood, many adults with CHD have residual abnormalities and complications, and face psychosocial and behavioral challenges . Hence, these patients cannot be considered to be cured and remain regular consumers of health care . In‐ and outpatient healthcare use is higher in adults with CHD as compared with the general population .…”
mentioning
confidence: 99%
“…Despite surgical repair during childhood, many adults with CHD have residual abnormalities and complications, and face psychosocial and behavioral challenges . Hence, these patients cannot be considered to be cured and remain regular consumers of health care . In‐ and outpatient healthcare use is higher in adults with CHD as compared with the general population .…”
mentioning
confidence: 99%
“…Although the results were calculated per patient year, we should acknowledge that the economic outcomes of this study remained subject to the competing risk of death. For example, hospital admissions costs are known to be higher when a patient dies during admission [18]. Therefore, the robustness of our results was checked by redoing our analyses, but with the exclusion of patients who died during the study period.…”
Section: Sensitivity Analysis: Exclusion Of Deceased Patientsmentioning
confidence: 99%
“…In addition to CHD severity and related medical conditions, mortality and survival rates for CHD are affected by the economic status of the country, [3][4][5][6][7][8] with high-income countries (HICs) having lower mortality and higher survival rates than lower-and middle-income countries (LMICs). Furthermore, The Global Burden of Disease Study 2017 showed a significant global disparity in CHD mortality rates.…”
Section: Introductionmentioning
confidence: 99%